Persepsi Wisatawan terhadap Objek Wisata Umbul Ponggok - Rini Wulandari (Academic Journal of Da'wa and Communication, 2022)
Umbul Ponggok is a swimming pool whose water comes from real springs. The underwater scenery that looks like the sea makes Umbul Ponggok visited by many tourists. The purpose of this study was to determine the perception of tourists about the Umbul Ponggok tourist attraction. This study uses survey methods and calculating perceptions using a Likert scale. There are 5 variables used to measure tourist perceptions. Based on the characteristics of tourists, Umbul Ponggok is most visited by tourists from outside the city of Klaten, most of which come for recreation. Tourists' perceptions of the quality of tourist objects are good, tourists' perceptions of the convenience of facilities, accommodation, amenities and accessibility are tourists feel comfortable, and tourists' perceptions of management and service satisfaction are satisfied tourists.